Animal cells dependent on exogenous phosphatidylcholine for membrane biogenesis. - Esko, J D (1982)
A Chinese hamster ovary cell (CHO) mutant (strain 58), defective in CDP-choline synthetase (cholinephosphate cytidylyltransferase; CTP:cholinephosphate cytidylyltransferase, EC 2.7.7.15), is temperature sensitive for growth and contains less than half of the normal amount of phosphatidylcholine under nonpermissive conditions [Esko, J. D. & Raetz, C. R. H. (1980) Proc. Natl. Acad. Sci. USA 77, 5192-5196]. We now report that the addition of 40 microM egg phosphatidylcholine or lysophosphatidylcholine to the medium suppresses the temperature sensitivity of mutant 58 and permits the growth of colonies at the restrictive temperature. Phospholipids with different polar headgroups, lipoprotein-bound phospholipids, sphingomyelin, and glycerophosphocholine do not support prolonged growth at 40 degrees C, whereas phosphatidylcholine analogs such as phosphatidyldimethylethanolamine, D-phosphatidylcholine, and beta-phosphatidylcholine are quite effective. A broad range of saturated phosphatidylcholines, especially those with fatty acids 12-18 carbons in length, suppresses the phenotype. Phospholipids containing ether-linked hydrocarbons are ineffective, whereas polyunsaturated phosphatidylcholines are toxic. Residual endogenous synthesis of phosphatidylcholine by the mutant is not stimulated under conditions of phenotypic bypass, but the uptake of exogenous lipid is enhanced considerably compared to the wild type. Our findings demonstrate that exogenous phospholipid can provide at least 50% of the phosphatidylcholine required for membrane biogenesis in animal cells and that uptake of exogenous phospholipids may be regulated.